HIV/AIDS epidemic in the State of Amazonas: characteristics and trends from 2001 to 2012 - Romina do Socorro Marques de Oliveira; Adele Schwartz Benzaken; Valeria Saraceni; Meritxell Sabidó (Revista da Sociedade Brasileira de Medicina Tropical, 2015)
A scoping review was conducted to describe the epidemiological characteristics of the human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) epidemic in the State of Amazonas, Brazil, from 2001 to 2012, and temporary patterns were estimated from surveillance data. The results suggest that in its third decade, the Amazon HIV/AIDS epidemic is far from being stabilized and displays rising AIDS incidence and mortality rates and late diagnoses. The data suggest that AIDS cases are hitting mostly young adults and have recently shifted toward men, both homosexual and heterosexual. AIDS cases among the indigenous people have remained stable and low. However, the epidemic has disseminated to the interior of the state, which adds difficulties to its control, given the geographical isolation, logistical barriers, and culturally and ethnically diverse population. Antiretroviral (ARV) therapy has been decentralized, but peripheral ARV services are still insufficient and too distant from people who need them. Recently, the expansion of point-of-care (POC) rapid HIV testing has been contributing to overcoming logistical barriers. Other new POC devices, such as the PIMA CD4 analyzer, will bring the laboratory to the patient. AIDS uniquely coexists with other tropical infections, sharing their epidemiological profiles. The increased demand for HIV/AIDS care services can only be satisfied through increased decentralization to peripheral health units, which can also naturally integrate care with other tropical infections and can promote a shift from vertical to integrated programming. Future challenges involve building surveillance data on HIV case notification and covering the spectrum of engagement in care, including adherence to treatment and follow-up loss.